Do they 'look' different(ly)? Dynamic face recognition in Malaysians: Chinese, Malays and Indians compared. - Wong, Hoo Keat; Keeble, David R. T.; Stephen, Ian D. (British Journal of Psychology)
Previous cross‐cultural eye‐tracking studies examining face recognition discovered differences in the eye movement strategies that observers employ when perceiving faces. However, it is unclear (1) the degree to which this effect is fundamentally related to culture and (2) to what extent facial physiognomy can account for the differences in looking strategies when scanning own‐ and other‐race faces. In the current study, Malay, Chinese and Indian young adults who live in the same multiracial country performed a modified yes/no recognition task. Participants' recognition accuracy and eye movements were recorded while viewing muted face videos of own‐ and other‐race individuals. Behavioural results revealed a clear own‐race advantage in recognition memory, and eye‐tracking results showed that the three ethnic race groups adopted dissimilar fixation patterns when perceiving faces. Chinese participants preferentially attended more to the eyes than Indian participants did, while Indian participants made more and longer fixations on the nose than Malay participants did. In addition, we detected statistically significant, though subtle, differences in fixation patterns between the faces of the three races. These findings suggest that the racial differences in face‐scanning patterns may be attributed both to culture and to variations in facial physiognomy between races.